Metal-free remote oxidative benzylic C−H amination of 4-methylanilides with N-fluorobenzenesulfonimide. Issue 10 (8th March 2018) - Yang, Yaocheng; Yu, Yanting; Wang, Yang; Zhang, Qian; Li, Dong
Abstract: A metal-free remote oxidative benzylic C−H amination of 4-methylanilides with N -fluorobenzenesulfonimide was reported. The reaction was promoted by a hypervalent iodine reagent and can be handled under mild and neutral conditions, providing the highly regioselective benzylic C−H amination products even with multi-substituted 4-methylanilides. It provided a novel and facile method for the construction of C(sp 3 )–N bonds. Graphical abstract: